2017
DOI: 10.4081/jphia.2016.584
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of hepatitis B surface antigen amongst pregnant women attending an antenatal clinic, Volta region, Ghana

Abstract: Hepatitis B virus (HBV) infection remains a global challenge, although there is currently a safe and effective vaccine available. HBV prevalence in Ghana is not well documented, but vary regionally from 4.8% to 12.3% in the general population, 10.8% to 12.7% in blood donors and about 10.6% in pregnant women. This puts Ghana among the high endemic countries in Africa. The study objective was to determine the sero-prevalence of HBs antigen (Ag) and HBeAg among pregnant women in the Ho municipality. Two hundred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
1
14
1
Order By: Relevance
“…However, similar studies conducted in the Volta region revealed a similar finding as observed in this study where age was a significant contributor of HBV infection among pregnant women. In fact, same studies reported that chances of women between 46 and 50 years of age becoming HBsAg carriers were high [21], further supporting the findings in this study where though not statistically significant, the computed odds ratio revealed that pregnant women aged forty years and above were 11.92 times more likely at risk of HBV infection (OR = 11:92, 95% CI = 0:5-284.30).…”
supporting
confidence: 88%
See 3 more Smart Citations
“…However, similar studies conducted in the Volta region revealed a similar finding as observed in this study where age was a significant contributor of HBV infection among pregnant women. In fact, same studies reported that chances of women between 46 and 50 years of age becoming HBsAg carriers were high [21], further supporting the findings in this study where though not statistically significant, the computed odds ratio revealed that pregnant women aged forty years and above were 11.92 times more likely at risk of HBV infection (OR = 11:92, 95% CI = 0:5-284.30).…”
supporting
confidence: 88%
“…Though Ghana among other African countries is considered an HBV endemic area [27,28], the current study suggests that individual districts may have different prevalence rates. Comparable intermediate prevalence rates of 2.4% and 2.2% among pregnant women attending antenatal clinic in the Volta Region and Yilo Krobo District, Eastern Region of Ghana, respectively, have been documented [18,21]. However, studies in other parts of Ghana recorded higher prevalence rates such as 16.7% in Kumasi [23], 10.6% in the Eastern Region [18], and 9.5% in the Asante Akim North Municipality of the Ashanti region [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies [19,27,31,35,37,40] were conducted among pregnant women with a total sample size of 5848 participants. The prevalence ranged from 2.4% to 16.7% with a pooled prevalence of 7.44% (CI; 4.71-11.55) and p<0.001 (S6 Appendix).…”
Section: Prevalence Of Hepatitis B Infection Among Pregnant Womenmentioning
confidence: 99%